Paleogeography of Africa through late jurasic-cretaceous Times - (:unkn) unknown (My University, 2008)
In the frame of various French research programs (CNRS), we are developing a paleogeographic database (ArcGIS) of the African plate (including Arabia) during the Late Jurassic- Cretaceous. Our main objective is to characterize and to quantify, at the scale of the continent, the relief changes and associated uplifts. - The database also includes for each times step: (1) the shelfbreak, (2) the shoreline (and the type of shoreline: fluvial, wave or tidal-dominated), (3) the bayline (and the lithology of the coastal plain: amount of evaporites or coals) and (4) the type of continental sedimentary systems (lakes: deep vs. shallow, channel rivers: bed load vs. suspended load rivers, alluvial fans) and the paleocurrents data available on the fluvial deposits. - From this, we defined the main river catchments and their divides, based on the paleocurrents data and the location of the river mouths on both lakes and seas. We also defined the uncertainties on catchment limits, their endoreic or exoreic caractere, and the erosional, by-passing and depositional domains for each catchments (plus the uncertainties on the limits between the different domains). - We integrate the boundary conditions such as plate kinematics and magmatism (a magmatism activity through time database is also compiled). From this, we defined the location of rift shoulders (if rifting), of highs of volcanic arcs (if subduction) or mountain belts (if accretion or collision), and of plateau associated with flood basalts (if plumes) or any other relief due to magmatic activity (alkaline small province, kimberlites?). The main tectonic events responsible of relief creations were during: - the Late Kimmeridgian-Early Tithonian (155-150 My; Yemen-Somalian rift initiation, oceanic accretion in the Indian Sea), - the intra Berriasian (145-140 My?; birth of the central African rift system from Niger to Kenya, uplift of the Western African Craton, drowning of the Atlantic carbonate platforms and grow
Keywords: African Research